834 Whole-Brain Visualization of Single-Neuron Activity During the Development of Neuropathic Pain. (1st April 2022) - Moosa, Shayan; Coley, Justin; Liu, Chang-Chia; Elias, W. Jeffrey; Kapur, Jaideep
Abstract : INTRODUCTION: Chronic neuropathic pain is severely disabling and difficult to treat. The pathophysiological mechanisms behind the transition from an acute to chronic neuropathic pain state are not well defined. METHODS: TRAP2 mice are genetically engineered to express tdTomato under dual control of a c-Fos gene promoter and estrogen receptor activation. Seven adult TRAP2 mice underwent unilateral chronic constrictive injury (CCI) of the sciatic nerve, while another six underwent exposure of the nerve without constriction. The mice were administered 4-OHT (to "TRAP" active neurons) one week, three weeks, or six weeks post-injury and maintained for six days before transcardial perfusion. Tissue clarification and confocal imaging/processing allowed for active neuronal populations in distinct brain regions to then be quantified and compared between groups. RESULTS: Allodynia developed in only the CCI groups, as confirmed by paw withdrawal thresholds. Active neuronal populations in the medial thalamus became significantly increased from baseline in all CCI groups. The anterior insula, secondary somatosensory cortex, and lateral parabrachial nucleus demonstrated significantly increased activity from baseline at one week post-injury, but this activity decreased at three and six weeks post-injury. Neuronal activity in the ventral orbital cortex was significantly increased from baseline only at three weeks post-injury, while activity in the anterior nucleus of the periventricular thalamus increased with time and became significantly elevated from baseline at three and six weeks post-injury. CONCLUSIONS: Our model demonstrates a clear increase in the neuronal activity of pain-related medial thalamic and cortical structures in mice who develop a chronic neuropathic pain state. The TRAP model is an ideal method to study brain plasticity during the transition from an acute pain state to chronic pain condition - enhancing our understanding of the mechanisms responsible for central sensitization to chronic neuropathic pain.